Ultralow-temperature high-rate sodium ion battery and preparation method thereof

By optimizing the composition and particle size of the positive and negative electrode material of the sodium ion battery and combining with conductive agent, the problem of poor discharge performance of sodium ion battery in low temperature environments is solved, and high-speed discharge and safety performance are improved, which is suitable for a wider range of applications. Application scenarios.

CN119297428APending Publication Date: 2025-01-10ZHUHAI PUNA TIMES NEW ENERGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411289901.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing sodium ion batteries have poor performance in high current discharge in low temperature environments, cannot support high-rate discharge, and insufficient charging temperature range, which limits their applications in the fields of start-stop power supply, new energy vehicles, etc.

Method used

Using a positive electrode slurry including P2 and O3 phase sodium ferromanganate oxide particles with specific proportions and particle sizes, combined with carbon black and CNT conductive agent, the negative electrode slurry and separator materials are optimized to prepare high-performance sodium ion batteries. Improves electrochemical performance and safety performance.

Benefits of technology

In an ultra-low temperature environment below -40℃, the discharge capacity retention rate of 10C is achieved to reach more than 80%. The safety performance has passed the needle-punch test and is suitable for a wider charging temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297428A_ABST
    Figure CN119297428A_ABST
Patent Text Reader

Abstract

The invention discloses an ultralow-temperature high-rate sodium ion battery and a preparation method thereof. The sodium-ion battery comprises a positive plate, a negative plate, a diaphragm, electrolyte and a shell, wherein the positive plate comprises a positive current collector and positive slurry coated on two sides of the positive current collector; the positive electrode slurry comprises 93 to 95 parts of an active substance, 1.1 to 3.0 parts of a binder, 2 to 4 parts of conductive carbon black, 0.6 to 1.5 parts of CNT conductive slurry and 0.1 to 0.3 part of a dispersant; the active substance is composed of P2-phase sodium ferro-manganate oxide particles and O3-phase sodium ferro-manganate oxide particles; the weight of the P2-phase sodium ferronickel manganate oxide particles is 5-20% of the weight of the O3 phase; the particle size D50 of the P2-phase nickel iron sodium manganate oxide particles is 8-11 [mu] m; and the particle size D50 of the O3-phase sodium ferro-nickel manganate oxide particles is 3-7 [mu] m. The electrochemical performance of the sodium ion battery under the ultralow temperature condition is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an ultra-low temperature high rate sodium ion battery and a preparation method thereof. Background Art

[0002] With the advancement of technology and the development of society, various types of application products are developing towards intelligence and multifunctionality, and the use environment is more complex. Batteries as energy sources are required to have better environmental applicability and rate performance. Lithium-ion batteries have attracted much attention due to their high operating voltage, high specific energy, and good cycle performance. They are widely used in consumer electronics, power tools, and energy storage. However, due to the shortage of lithium resources and the high and unstable price of upstream raw material lithium carbonate, cost issues have limited the application of lithium-ion batteries in certain fields to a certain extent. Sodium resources are abundant, low-priced, and the supply is guaranteed. The production equipment of sodium-ion batteries is basically the same as that of lithium-ion batteries. Therefore, more and more companies are turning to sodium-ion battery research with better cost performance.

[0003] The charging temperature of conventional sodium-ion batteries is 0℃ to +45℃, the discharge temperature is -40℃ to +60℃, and the rate performance is average. And when used for discharge with a slightly larger current in a low temperature environment (below -20℃), the battery polarization increases, the discharge voltage is reached too early, and no electricity can be discharged. It can only support discharge with a small current below 1C, does not support large current discharge, and cannot meet low-temperature charging below 0℃. However, many application areas, especially start-stop power supplies, new energy vehicles, military equipment and other scenarios, require high-rate discharge performance at low temperatures and have a wider charging temperature range. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the object of the present invention is to provide an ultra-low temperature and high rate sodium ion battery, which greatly improves the electrochemical performance of the sodium ion battery under ultra-low temperature conditions.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides an ultra-low temperature high rate sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on both sides of the positive electrode current collector;

[0007] In parts by weight, the positive electrode slurry comprises 93-95 parts of active material, 1.1-3.0 parts of binder, 2-4 parts of conductive carbon black, 0.6-1.5 parts of CNT conductive slurry, and 0.1-0.3 parts of dispersant;

[0008] The active material consists of P2 phase sodium nickel iron manganate oxide particles and O3 phase sodium nickel iron manganate oxide particles; wherein the weight of the P2 phase sodium nickel iron manganate oxide particles is 5% to 20% of the O3 phase sodium nickel iron manganate oxide particles; the particle size D50 of the P2 phase sodium nickel iron manganate oxide particles is 8 to 11 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide particles is 3 to 7 μm.

[0009] Preferably, the binder is polyvinylidene fluoride; and the dispersant is PVP.

[0010] Preferably, the negative electrode plate comprises a negative electrode current collector and a negative electrode slurry coated on both sides of the negative electrode current collector;

[0011] In parts by weight, the negative electrode slurry includes 93-95 parts of hard carbon, 0.5-2 parts of sodium carboxymethyl cellulose, 1.5-3.0 parts of a binder, and 2.0-4.0 parts of a conductive agent.

[0012] Preferably, the diaphragm is one of polypropylene, polyethylene, and polyethylene coated with nano-aluminum oxide ceramic powder or boehmite on the surface.

[0013] Preferably, the electrolyte comprises 14 to 18 parts of sodium salt, 75 to 80 parts of organic solvent, and 3 to 6 parts of additives in parts by weight.

[0014] Preferably, the sodium salt includes two or three of sodium hexafluorophosphate, sodium difluorophosphate, and sodium difluorooxalatoborate; the organic solvent includes three or more of ethyl methyl carbonate, ethyl propionate, propylene carbonate, and ethylene carbonate; and the additive is at least one of sodium bis(fluorosulfonyl)imide, 1,3-propane sultone, fluoroethylene carbonate, and vinyl sulfate.

[0015] The present invention also provides a method for preparing the ultra-low temperature high rate sodium ion battery, comprising the following steps:

[0016] Prepare positive electrode slurry, apply the positive electrode slurry on both sides of the positive electrode current collector, and apply the double-sided surface density of 130-200 g / ㎡, and obtain the positive electrode sheet after rolling, slitting and sheeting;

[0017] Prepare negative electrode slurry, apply the negative electrode slurry on both sides of the negative electrode current collector, and apply the double-sided surface density of 60-100 g / ㎡, and obtain the negative electrode sheet after rolling, slitting and sheeting;

[0018] The positive electrode sheet, the negative electrode sheet and the separator are wound, assembled, welded, baked, injected, formed and divided to prepare a sodium ion battery.

[0019] Preferably, the preparation of the positive electrode slurry is specifically as follows:

[0020] (1) Add 60-70 parts by weight of NMP and 1.1-3.0 parts by weight of a binder into a double planetary mixer, and stir at a revolution of 15-25 rpm and a rotation of 2000-2500 rpm for 120-210 min. The resulting solution is called positive electrode glue;

[0021] (2) adding 2.0 to 4.0 parts by weight of conductive carbon black to the positive electrode glue prepared in step (1), stirring at a revolution of 15 to 25 rpm and a rotation of 2000 to 2500 rpm for 50 to 70 min to obtain a positive electrode conductive glue;

[0022] (3) adding 5 to 15 parts by weight of sodium nickel iron manganese oxide particles of P2 phase structure to the positive electrode conductive glue prepared in step (2), and stirring at a revolution of 15 to 25 rpm and a rotation of 1500 to 2000 rpm for 10 to 20 minutes;

[0023] (4) adding 85 to 95 parts by weight of sodium nickel iron manganate oxide particles having an O3 phase structure to the slurry prepared in step (3), and stirring at a revolution of 15 to 25 rpm and a rotation of 1500 to 2000 rpm for 40 to 60 min;

[0024] (5) adding 0.1-0.3 parts by weight of PVP and 0.6-1.5 parts by weight of CNT conductive slurry, and continuing stirring at 20-30 rpm and 2500-3000 rpm for 120-200 min;

[0025] (6) NMP is added to adjust the viscosity, and the mixture is stirred at a revolution of 20 to 30 rpm and an autorotation of 2500 to 3000 rpm for 30 to 40 min. After the stirring is completed, the slurry is evacuated to obtain a positive electrode slurry.

[0026] Preferably, the preparation of the negative electrode slurry is specifically as follows:

[0027] (1) adding 45-55 parts by weight of deionized water and 0.5-2 parts by weight of sodium carboxymethyl cellulose into a double planetary mixer, stirring at a revolution of 15-25 rpm and a rotation of 2000-2500 rpm for 120-180 min to obtain a negative electrode glue solution; dividing the negative electrode glue solution into two parts;

[0028] (2) adding 2 to 4 parts by weight of a conductive agent to a portion of the negative electrode glue prepared in step (1), stirring at a revolution of 15 to 25 rpm and a rotation of 2000 to 2500 rpm for 40 to 60 minutes to obtain a negative electrode conductive glue;

[0029] (3) adding 93-95 parts by weight of hard carbon to the negative electrode conductive glue prepared in step (2), and stirring at a revolution of 15-25 rpm and a rotation of 1500-2000 rpm for 30-60 min;

[0030] (4) Add another portion of the negative electrode glue in step (1) and deionized water, and continue stirring at a revolution of 20 to 25 rpm and a rotation of 1500 to 2000 rpm for 120 to 150 min;

[0031] (5) adding 1.5 to 3 parts by weight of a styrene acrylic binder, stirring at a revolution speed of 10 to 15 rpm and a rotation speed of 300 to 500 rpm for 30 to 40 minutes;

[0032] (6) After the stirring is completed, the slurry obtained in step (5) is evacuated to obtain a negative electrode slurry.

[0033] The present invention also provides a positive electrode slurry for a lithium ion battery, which comprises, by weight, 93 to 95 parts of an active material, 1.1 to 3.0 parts of a binder, 2 to 4 parts of conductive carbon black, 0.6 to 1.5 parts of a CNT conductive slurry, and 0.1 to 0.3 parts of a dispersant;

[0034] The active material consists of P2 phase sodium nickel iron manganate oxide particles and O3 phase sodium nickel iron manganate oxide particles; wherein the weight of the P2 phase sodium nickel iron manganate oxide particles is 5% to 20% of the O3 phase sodium nickel iron manganate oxide particles; the particle size D50 of the P2 phase sodium nickel iron manganate oxide particles is 8 to 11 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide particles is 3 to 7 μm.

[0035] Preferably, the P2 phase sodium nickel iron manganate oxide particles have a specific surface area of ​​0.5 to 1.3 m2 / g and a gram specific capacity of ≥120 mAh / g; the O3 phase sodium nickel iron manganate oxide particles have an ideal structure with high conductivity, secondary particle morphology, a specific surface area of ​​0.3 to 1.0 m2 / g, and a tap density of ≥1.2 g / cm 3 , gram-specific capacity ≥130mAh / g.

[0036] Preferably, the hard carbon is a coated and modified biomass hard carbon with a high slope area capacity, and its particle size D50 is preferably 5 to 9 μm, and the specific surface area is 1 to 8 m 2 / g, tap density 0.7~0.9g / cm 3 ; The binder is a styrene acrylic binder, which helps to reduce interface impedance and improve rate performance; the conductive agent is one or both of carbon black or carbon nanotube composite conductive paste.

[0037] Preferably, the positive electrode current collector is aluminum foil; and the negative electrode current collector is copper foil.

[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0039] (1) The ultra-low temperature and high rate sodium ion battery of the present invention can achieve discharge at a rate of 10C in an ultra-low temperature environment of -40°C with a capacity retention rate of more than 80% by optimizing the composition formula of the positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte, and the preparation process; discharge at a rate of 30C in a low temperature environment of -30°C with a capacity retention rate of more than 80%; and charge at 0.2C in a low temperature environment of -20°C. It has passed safety performance tests such as needle puncture and has high safety performance.

[0040] (2) The ultra-low temperature and high rate sodium ion battery of the present invention optimizes the composition and particle size range of the positive and negative electrode slurries, which is beneficial to the rapid escape and embedding of sodium ions and reduces electrochemical polarization and diffusion impedance.

[0041] (3) The ultra-low temperature and high rate sodium ion battery of the present invention uses two kinds of sodium nickel iron manganese oxide materials with different phase structures and appropriate physical properties, which are compounded in a certain proportion, as positive electrode active materials, taking into account the low temperature and high rate discharge performance and energy density of the sodium ion battery.

[0042] (4) In the ultra-low temperature and high rate sodium ion battery of the present invention, the positive and negative electrode sheets adopt a composite conductive slurry of carbon black and carbon nanotubes. The two conductive agents work synergistically to improve the conductivity of the electrode sheets and reduce polarization. Since the pH of the positive electrode material is relatively high, the slurry tends to become jelly-like. The present invention adds an appropriate amount of PVP dispersant to ensure better slurry dispersion effect and performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The 0.2C charge / 1C discharge cycle curves of the sodium ion batteries of Example 1, Example 2 and Comparative Example of the present invention at -20°C. DETAILED DESCRIPTION

[0044] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0045] Example 1

[0046] The ultra-low temperature high rate sodium ion battery of this embodiment includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode slurry coated on both sides of the positive electrode current collector; the positive electrode current collector is aluminum foil. The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on both sides of the negative electrode current collector; the negative electrode current collector is copper foil.

[0047] In this embodiment, the positive electrode slurry contains, by weight: 6% P2 phase sodium nickel iron manganese oxide (D50 is 8.3μm), 88.2% O3 phase sodium nickel iron manganese oxide (D50 is 5.2μm), 1.5% binder PVDF, 3.5% carbon black, 0.7% CNT conductive slurry, and 0.1% PVP; the negative electrode sheet contains (calculated by weight percentage of solid matter): 93.6% coated modified hard carbon (D50 is 7.3um), 2.5% conductive agent carbon black, 1.2% sodium carboxymethyl cellulose, and 2.7% styrene acrylic binder.

[0048] In this embodiment, the diaphragm is a polyethylene diaphragm with nano-scale aluminum oxide ceramic powder coated on the surface.

[0049] In this embodiment, the electrolyte includes sodium salt (sodium hexafluorophosphate, sodium difluorophosphate), organic solvent (ethyl methyl carbonate, propylene carbonate, ethylene carbonate) and additives (sodium bisfluorosulfonyl imide, fluoroethylene carbonate, vinyl sulfate). Specifically, by weight, it contains 14% sodium hexafluorophosphate, 0.5% sodium difluorophosphate, 80% organic solvent in total, 3% sodium bisfluorosulfonyl imide, 1.5% fluoroethylene carbonate, and 1% vinyl sulfate.

[0050] The steps for preparing the ultra-low temperature rate sodium ion cylindrical battery with a rated capacity of 1100 mAh in this embodiment are as follows:

[0051] Prepare positive electrode slurry, apply the positive electrode slurry on both sides of the positive electrode current collector, and apply the double-sided surface density of 160g / ㎡, and obtain the positive electrode sheet after rolling, slitting and sheeting;

[0052] Prepare negative electrode slurry and apply the negative electrode slurry on both sides of the negative electrode current collector with a double-sided surface density of 80g / m 2 , after rolling, slitting and sheeting, the negative electrode sheet is obtained;

[0053] The positive electrode sheet, the negative electrode sheet and the separator are wound, assembled, welded, baked, injected, formed, and divided into different volumes to form a sodium ion cylindrical battery.

[0054] In this embodiment, the positive electrode slurry is prepared as follows:

[0055] (1) Add NMP and binder into a double planetary mixer and stir for 180 min at a revolution of 20 rpm and a rotation of 2200 rpm. The obtained solution is called positive electrode glue;

[0056] (2) adding conductive carbon black to the positive electrode glue prepared in step (1), stirring at 20 rpm and 2200 rpm for 60 min to obtain a positive electrode conductive glue;

[0057] (3) adding sodium nickel iron manganese oxide of P2 phase structure to the positive electrode conductive glue prepared in step (2), and stirring at 20 rpm and 2200 rpm for 15 min;

[0058] (4) adding the sodium nickel iron manganate oxide having an O3 phase structure to the slurry prepared in step (3), and stirring at a revolution of 20 rpm and a rotation of 1800 rpm for 50 min;

[0059] (5) Add PVP and CNT conductive slurry, and continue stirring at 25 rpm and 2800 rpm for 150 min;

[0060] (6) A certain amount of NMP was added to adjust the viscosity, and the mixture was stirred at 25 rpm and 2800 rpm for 35 min. After the stirring was completed, the slurry was vacuumed to obtain a positive electrode slurry.

[0061] In this embodiment, the negative electrode slurry is prepared as follows:

[0062] (1) Add deionized water and sodium carboxymethyl cellulose into a double planetary mixer and stir for 150 min at a revolution of 20 rpm and a rotation of 2500 rpm. The obtained solution is called negative electrode glue solution, and part of the glue solution is taken out for later steps;

[0063] (2) adding a conductive agent to part of the negative electrode glue prepared in step (1), stirring at 20 rpm and 2200 rpm for 50 min to obtain a negative electrode conductive glue;

[0064] (3) adding hard carbon to the negative electrode conductive gel prepared in step (2), and stirring at 20 rpm and 1800 rpm for 40 min;

[0065] (4) After completing step (3), add the spare negative electrode glue taken out in step (1) and add an appropriate amount of deionized water, and continue to stir at a revolution of 22 rpm and a rotation of 1800 rpm for 130 min;

[0066] (5) Add styrene acrylic binder and stir at 12 rpm and 400 rpm for 35 min;

[0067] (6) After the stirring is completed, the slurry obtained in step (5) is evacuated to obtain a negative electrode slurry.

[0068] Example 2

[0069] The ultra-low temperature rate sodium ion cylindrical battery A2 with a rated capacity of 1100 mAh and the preparation method thereof in this embodiment, except for the following features, other components and preparation process are the same as those in Example 1:

[0070] The particle size D50 of the P2 phase sodium nickel iron manganate oxide is 8.3 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide is 5.2 μm.

[0071] Comparative Example 1

[0072] The preparation method of the rate-type sodium ion cylindrical battery B1 with a rated capacity of 1100 mAh in this comparative example is the same as that of Example 1 except for the following features:

[0073] The particle size D50 of the P2 phase sodium nickel iron manganate oxide is 9.0 μm, and the particle size D50 of the O3 phase sodium nickel iron manganate oxide is 9.0 μm.

[0074] The high rate discharge performance of the ultra-low temperature rate sodium ion cylindrical battery A1 (sample numbers A1-1, A1-2, A1-3) prepared in Example 1, the ultra-low temperature rate sodium ion cylindrical battery A2 (sample numbers A2-1, A2-2, A2-3) prepared in Example 2, and the rate sodium ion cylindrical battery B1 (sample numbers B1-1, B1-2, B1-3) prepared in Comparative Example 1 under low temperature environment is shown in Table 1. The 0.2C charge / 1C discharge cycle curve at -20°C is shown in Table 1. Figure 1 shown.

[0075] Table 1 Comparison of high rate discharge performance under low temperature environment

[0076]

[0077] As shown in Table 1, in Examples 1 and 2, the particle size of the P2 phase sodium nickel iron manganate oxide in the positive electrode slurry is larger than that of the O3 phase sodium nickel iron manganate oxide, and the following conditions are met: the particle size D50 of the P2 phase sodium nickel iron manganate oxide particles is 8 to 11 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide particles is 3 to 7 μm. Compared with Comparative Example 1 in which the particle size of both phases in the positive electrode slurry is 9.0 μm, the electrochemical performance of the sodium ion batteries of Examples 1 and 2 in low temperature, especially in ultra-low temperature environments of -30°C and -40°C, is significantly improved.

[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An ultra-low temperature high rate sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on both sides of the positive electrode current collector; In parts by weight, the positive electrode slurry comprises 93-95 parts of active material, 1.1-3.0 parts of binder, 2-4 parts of conductive carbon black, 0.6-1.5 parts of CNT conductive slurry, and 0.1-0.3 parts of dispersant; The active material consists of P2 phase sodium nickel iron manganate oxide particles and O3 phase sodium nickel iron manganate oxide particles; wherein the weight of the P2 phase sodium nickel iron manganate oxide particles is 5% to 20% of the O3 phase sodium nickel iron manganate oxide particles; the particle size D50 of the P2 phase sodium nickel iron manganate oxide particles is 8 to 11 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide particles is 3 to 7 μm.

2. The ultra-low temperature high rate sodium ion battery according to claim 1, characterized in that: The binder is polyvinylidene fluoride; the dispersant is PVP.

3. The ultra-low temperature and high rate sodium ion battery according to claim 1, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode slurry coated on both sides of the negative electrode current collector; In parts by weight, the negative electrode slurry includes 93-95 parts of hard carbon, 0.5-2 parts of sodium carboxymethyl cellulose, 1.5-3.0 parts of a binder, and 2.0-4.0 parts of a conductive agent.

4. The ultra-low temperature and high rate sodium ion battery according to claim 1, characterized in that: The diaphragm is one of polypropylene, polyethylene, and polyethylene with nano-aluminum oxide ceramic powder or boehmite coated on the surface.

5. The ultra-low temperature and high rate sodium ion battery according to claim 1, characterized in that: In parts by weight, the electrolyte includes 14 to 18 parts of sodium salt, 75 to 80 parts of organic solvent, and 3 to 6 parts of additives.

6. The ultra-low temperature high rate sodium ion battery according to claim 5, characterized in that: The sodium salt includes two or three of sodium hexafluorophosphate, sodium difluorophosphate, and sodium difluorooxalatoborate; the organic solvent includes three or more of ethyl methyl carbonate, ethyl propionate, propylene carbonate, and ethylene carbonate; and the additive is at least one of sodium bis(fluorosulfonyl)imide, 1,3-propane sultone, fluoroethylene carbonate, and vinyl sulfate.

7. The method for preparing the ultra-low temperature high rate sodium ion battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: Prepare positive electrode slurry, apply the positive electrode slurry on both sides of the positive electrode current collector, and apply the double-sided surface density of 130-200 g / ㎡, and obtain the positive electrode sheet after rolling, slitting and sheeting; Prepare negative electrode slurry, apply the negative electrode slurry on both sides of the negative electrode current collector, and apply the double-sided surface density of 60-100 g / ㎡, and obtain the negative electrode sheet after rolling, slitting and sheeting; The positive electrode sheet, the negative electrode sheet and the separator are wound, assembled, welded, baked, injected, formed and divided to prepare a sodium ion battery.

8. The method for preparing an ultra-low temperature high rate sodium ion battery according to claim 7, characterized in that: The preparation of the positive electrode slurry is specifically as follows: (1) Add 60-70 parts by weight of NMP and 1.1-3.0 parts by weight of a binder into a double planetary mixer, and stir at a revolution of 15-25 rpm and a rotation of 2000-2500 rpm for 120-210 min. The resulting solution is called positive electrode glue; (2) adding 2.0 to 4.0 parts by weight of conductive carbon black to the positive electrode glue prepared in step (1), stirring at a revolution of 15 to 25 rpm and a rotation of 2000 to 2500 rpm for 50 to 70 min to obtain a positive electrode conductive glue; (3) adding 5 to 15 parts by weight of sodium nickel iron manganese oxide particles of P2 phase structure to the positive electrode conductive glue prepared in step (2), and stirring at a revolution of 15 to 25 rpm and a rotation of 1500 to 2000 rpm for 10 to 20 minutes; (4) adding 85 to 95 parts by weight of sodium nickel iron manganate oxide particles having an O3 phase structure to the slurry prepared in step (3), and stirring at a revolution of 15 to 25 rpm and a rotation of 1500 to 2000 rpm for 40 to 60 min; (5) adding 0.1-0.3 parts by weight of PVP and 0.6-1.5 parts by weight of CNT conductive slurry, and continuing stirring at 20-30 rpm and 2500-3000 rpm for 120-200 min; (6) NMP is added to adjust the viscosity, and the mixture is stirred at a revolution of 20 to 30 rpm and an autorotation of 2500 to 3000 rpm for 30 to 40 min. After the stirring is completed, the slurry is evacuated to obtain a positive electrode slurry.

9. The method for preparing an ultra-low temperature high rate sodium ion battery according to claim 7, characterized in that: The preparation of the negative electrode slurry is specifically as follows: (1) adding 45-55 parts by weight of deionized water and 0.5-2 parts by weight of sodium carboxymethyl cellulose into a double planetary mixer, stirring at a revolution of 15-25 rpm and a rotation of 2000-2500 rpm for 120-180 min to obtain a negative electrode glue solution; dividing the negative electrode glue solution into two parts; (2) adding 2 to 4 parts by weight of a conductive agent to a portion of the negative electrode glue prepared in step (1), stirring at a revolution of 15 to 25 rpm and a rotation of 2000 to 2500 rpm for 40 to 60 minutes to obtain a negative electrode conductive glue; (3) adding 93-95 parts by weight of hard carbon to the negative electrode conductive glue prepared in step (2), and stirring at a revolution of 15-25 rpm and a rotation of 1500-2000 rpm for 30-60 min; (4) Add another portion of the negative electrode glue in step (1) and deionized water, and continue stirring at a revolution of 20 to 25 rpm and a rotation of 1500 to 2000 rpm for 120 to 150 min; (5) adding 1.5 to 3 parts by weight of a styrene acrylic binder, stirring at a revolution speed of 10 to 15 rpm and a rotation speed of 300 to 500 rpm for 30 to 40 minutes; (6) After the stirring is completed, the slurry obtained in step (5) is evacuated to obtain a negative electrode slurry.

10. A positive electrode slurry for a lithium ion battery, characterized in that: In parts by weight, it contains 93-95 parts of active material, 1.1-3.0 parts of binder, 2-4 parts of conductive carbon black, 0.6-1.5 parts of CNT conductive paste, and 0.1-0.3 parts of dispersant; The active material consists of P2 phase sodium nickel iron manganate oxide particles and O3 phase sodium nickel iron manganate oxide particles; wherein the weight of the P2 phase sodium nickel iron manganate oxide particles is 5% to 20% of the O3 phase sodium nickel iron manganate oxide particles; the particle size D50 of the P2 phase sodium nickel iron manganate oxide particles is 8 to 11 μm; the particle size D50 of the O3 phase sodium nickel iron manganate oxide particles is 3 to 7 μm.

Citation Information

Cited By

  • Low-temperature high-power discharge sodium battery and preparation method thereof

    CN119864494A